Developing LQR to control speed motor using matlab GUI - Shamsul Nizam, Mohd Yusof@ Hamid (2008)
This project is mainly upon developing Linear Quadratic Regulator (LQR) controller and controlling it through software. In the software part, MATLAB GUI is been implemented to control the whole LQR system. In addition, a servo motor is attached as a hardware module to show the resultant of the LQR controller. The ability of the controller on the servo motor is, it is capable to manipulate and control the rotating speed of the motor. Thus it could also regulate the value from the error that occurs at output so that the value is stabilized as same as the input. Application of feedback system is applied in the MATLAB GUI itself before interfacing it with the servo motor using DAQ Card. The output from the MATLAB is then sent to the input of the DAQ Card through the Analog pin. A generation of signal from output at DAQ Card through the Analog pin subsequently enters to the motor driver. Driving the motor with the signal provided, it will send a feedback signal back to the system to be compared with the initial input. The whole system built from the simulink modeling through the software MATLAB.